IGFBP-4: a promising biomarker for lung cancer - Savaş, irem nur; Öztürk, Akın; Kavas, Murat; Bulut, İsmet; Alparslan, Sümeyye; Aydoğan Eroğlu, Selma; Atinkaya Baytemir, Cansel; Kolay, Murat; Coşkun, Abdurrahman (Journal of Medical Biochemistry, 2020)
Background: Insulin-like growth factor binding protein-4 (IGFBP-4), a member of the insulin like growth factor (IGF) family, transports and regulates the activity of IGFs. Pregnancy associated protein-A (PAPP-A) has proteolytic activity towards IGFBP-4 and both have been associated with a variety of cancers, including lung. We aimed to evaluate the utility of IGFBP-4 and PAPP-A as potential biomarkers in lung cancer.Materials and Methods: Eighty-three volunteers, including 60 patients with lung cancer and 23 healthy individuals, were included. Patients with lung cancer were selected based on treatment status, histological subgroup, and stage of the disease. Enzyme-linked immunosorbent assays were used to assess serum levels of IGFBP-4 and PAPP-A, whereas IGF-1 levels were measured using a chemiluminescent immunometric assay.Results: Serum IGFBP-4 levels in all patient groups, regardless of treatment status and histological differences, were significantly higher than those in the control group (p < 0.005). However, serum PAPP-A levels in the untreated patient group were found to be higher than those in the control group, and this difference was not statistically significant (p = 0.086).Conclusion: Serum PAPP-A and IGFBP-4 levels are elevated in lung cancer. However, IGFBP-4 may have a better potential than PAPP-A as a lung cancer biomarker.